Produtividade da aveia branca cv. IPR 126 submetida à níveis e formas de parcelamento de nitrogênio em cobertura, com e sem cortes - Haselbauer, Franciele Rechembach (2017)
The intensification of production in integrated production systems, is based on the sustainability of the same, seeking the best arrangements to sustain good results. Fertilization is of extreme importance for the success in productivity, being nitrogenous that requires more attention in the production, mainly of grasses. In cultivation of pastures there is often negligence in fertilization, being greater when it comes to coverage. Based on this premise, the objective of this work is to find an answer for the nitrogen fertilization applied in white oats, as well as if this fertilization is more responsive in single or split doses, in a system of cuts and for vegetal cover. The experiment was developed in UTFPR-DV, in a 2 x 6 factorial design (management x nitrogen levels), randomized blocks, with three replicates and subdivided plots. The plots received four nitrogen doses 0, 60, 120 and 180 kg ha-1 of N associated to three forms of fertilizer application (single dose application as well as the splitting of doses of 120 and 180 kg ha-1 of N in two and three applications of 60 kg N ha-1 respectively). Nitrogen fertilization was carried out in the haul, with urea (45% N) being the source of nitrogen used. The evaluations carried out in the oats were determination of accumulation rate, dry matter, recovery rate and efficiency of nitrogen use and crude protein content. The data were submitted to analysis of variance and when verified by means of the F test, the means were compared by the Tukey test at 5% error probability. The mean accumulation rate ranged from 39.36 to 59.42 kg ha-1 of DM for uncut and 41.73 to 62.67 kg ha-1 of DM with cuts. The dry matter yield for uncrowded accumulated varied from 6240 to 10266.67 kg ha-1 of DM at the studied levels, with cuts, from 4865 to 7593.33 kg ha-1 of MS. The maximum technical efficiency was obtained with 149 kg ha-1 of N. The efficiency of the use of nitrogen decreased with the increase of the nitrogen levels. In general, the recovery rate also decreased with increasing nitrogen levels. The crude protein varied for the plots without cuts of 12.1 to 16.06% and with cuts of 13.41 to 16.92%. It was concluded that there was immobilization of nitrogen applied at higher doses, being more expressive in treatments that did not receive cuts. From 120 kg ha-1 of N, the splitting can be interesting when there is no temporal loss due to immobilization.